Answer:
your worse nightmare MATH
Step-by-step explanation:
I’m hoping you are talking about:
Factor -1/2 out of -1/2x + 6
If so then the answer is
-1/2(x-3)
We are told that f(x) = x + 2. We want to find
.
Squaring f(x) on one side means we square x + 2 on the other.
So,
f(x) = x + 2
(f(x))² = (x + 2)²
= (x + 2)(x + 2)
We can use FOIL to square x + 2. The first terms multiply to x², the outside terms to 2x, the inside terms to 2x and the last terms to 4.
= x² + 2x + 2x + 4
= x² + 4x + 4
So [f(x)]² = x² + 4x + 4
Complete Question
The complete question is shown on the first uploaded
Answer:
is not a solution of the differential equation
is not a solution of the differential equation
is not a solution of the differential equation
Step-by-step explanation:
The differential equation given is ![y'' + y' = cos2x](https://tex.z-dn.net/?f=y%27%27%20%2B%20y%27%20%3D%20cos2x)
Let consider the first equation to substitute
![y_1 = cosx +sinx](https://tex.z-dn.net/?f=y_1%20%20%3D%20cosx%20%20%2Bsinx)
![y_1' = -sinx +cosx](https://tex.z-dn.net/?f=y_1%27%20%20%3D%20-sinx%20%20%2Bcosx)
![y_1'' = -cosx -sinx](https://tex.z-dn.net/?f=y_1%27%27%20%20%3D%20-cosx%20-sinx)
So
![y_1'' - y_1' = -cosx -sinx -sinx +cosx](https://tex.z-dn.net/?f=y_1%27%27%20-%20y_1%27%20%20%3D%20-cosx%20-sinx%20-sinx%20%20%2Bcosx)
![y_1'' + y_1' = -2sinx](https://tex.z-dn.net/?f=y_1%27%27%20%2B%20y_1%27%20%20%3D%20-2sinx%20)
So
![-2sinx \ne cos2x](https://tex.z-dn.net/?f=%20%20-2sinx%20%5Cne%20%20cos2x%20)
This means that
is not a solution of the differential equation
Let consider the second equation to substitute
![y_2 = cos2x](https://tex.z-dn.net/?f=y_2%20%3D%20%20cos2x)
![y_2' = -2sin2x](https://tex.z-dn.net/?f=y_2%27%20%3D%20%20-2sin2x)
![y_2'' = -4cos2x](https://tex.z-dn.net/?f=y_2%27%27%20%3D%20%20-4cos2x)
So
![y_2'' + y_2' = -4cos2x-2sin2x](https://tex.z-dn.net/?f=y_2%27%27%20%2B%20y_2%27%20%20%3D%20-4cos2x-2sin2x%20)
So
![-4cos2x-2sin2x \ne cos2x](https://tex.z-dn.net/?f=%20-4cos2x-2sin2x%20%5Cne%20%20cos2x%20)
This means that
is not a solution of the differential equation
Let consider the third equation to substitute
![y_3 = sin 2x](https://tex.z-dn.net/?f=y_3%20%3D%20%20sin%202x)
![y_3' = 2cos 2x](https://tex.z-dn.net/?f=y_3%27%20%3D%20%202cos%202x)
![y_3'' = -4sin2x](https://tex.z-dn.net/?f=y_3%27%27%20%3D%20%20-4sin2x)
So
![y_3'' + y_3' = -4sin2x - 2cos2x](https://tex.z-dn.net/?f=y_3%27%27%20%2B%20y_3%27%20%20%3D%20-4sin2x%20%20-%202cos2x%20)
So
This means that
is not a solution of the differential equation
Answer:
99![cm^{2}](https://tex.z-dn.net/?f=cm%5E%7B2%7D)
Step-by-step explanation:
12x4=48
12x3=36
12-4-5=3
3x5=15
48+36+15=99